Наша Таня громко плачет - Барто Агния Львовна (Самовар, 2006)
Экземпляры: аб. (20230526) / Инвентарный номер: 63663 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5